ANALISIS KEMAMPUAN MENYUSUN CERITA PENDEK PADA SISWA KELAS III SEKOLAH DASAR HKBP SEI MATI - Harumi Siregar; Indri Aulia; Shiva Khairina Hamidah Batubara; Erwati Napitupulu; Feby Aulia Khairunnisa (Bajang Institute, 2025)
This study aims to analyze the short story writing skills of third-grade students at SD HKBP Sei Mati. A descriptive qualitative method was employed,involving 20 student-written short stories.the analysis focused on five aspects :originality,relevance of content to the title,text coherence,vocabulary choice,and grammar usage.The results indicated that students’weiting abilities ranged from good to very good,The highest scores were foud in content relevance,coherence,and grammar,while originality and vocabulary require further improvement.these findings highlight thr nrrd for more creative and interactive writing instruction to enhance studentd’idea development and vocabulary use.this research is expected to serve as a reference for teachers in improving the effectiveness of weiting lessons in elementary schools